Water, sanitary and waste services for buildings - Wise, Alan Frederick Edward
Water, sanitary and waste services represent a substantial proportion of the cost of construction, averaging 10% of the capital costs of building and with continuing costs in operation and maintenance. Nevertheless, they are often regarded as a 'Cinderella' within the building process. Parts of many different codes and regulations impact on these services, making an overall viewpoint more difficult to get. This new edition of this classic text draws together material from a variety of sources to provide the comprehensive coverage not available elsewhere. It is a resource for the sound design, o.